A Methodology for Assessing Groundwater Pollution Hazard by Nitrates from Agricultural Sources: Application to the Gallocanta Groundwater Basin (Spain). - Orellana Macías, José María; Perles-Roselló, María Jesús; Causapé, Jesús (MDPI, 2021)
Groundwater pollution by nitrates from agricultural sources is a common environmental issue. In order to support risk analysis, hazard maps are used to classify land uses according to their potential of pollution. The aim of this study is to propose a new hazard index based on nitrogen input and its connection with nitrate concentration in groundwater. The effectiveness of the Nitrogen Input Hazard Index was tested in the Gallocanta Groundwater Basin (Spain), a highly polluted area, declared as a Nitrate Vulnerable Zone. Agricultural data at a plot scale were used to estimate the nitrogen fertilizer requirement of each crop, and the correlation between nitrogen input and nitrate concentration in groundwater was explored. The resulting hazard map allows us to delimit the most hazardous areas, which can be used to implement more accurate nitrate pollution control programs. The index was proven to successfully estimate nitrogen input influence over groundwater nitrate concentration, and to be able to create hazard maps. The criterion used to create categories was empirically based on nitrate concentration thresholds established by the EU Nitrate Directive. The Nitrogen Input Hazard Index may be a useful tool to support risk analyses of agricultural activities in vulnerable areas, where nitrate pollution could endanger human water supply.
Keywords: Nitratos; Aguas subterráneas - Contaminación - Gallocanta (España, Laguna); Nitrogen Input Hazard Index; Nitrate Vulnerable Zone 1. Introduction; Nitrogen requirement; Hazard index; Hazard map